Modular effect of melatonin on diabetic heart disease in rats - B.J. Nascimento; M.V. Silva; É.R. Alves; Y.B. Santos; I.M.F. Melo; B.M. Tenório; C.J.C. Lapa-Neto; A.M.G. Santos; V. Wanderley-Teixeira; Á.A.C Teixeira (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT The aim of this study was to analyze the effects of melatonin administration on the hearts of rats induced with diabetes. Twenty male Wistar albino rats, 70 days old, were divided into the following groups: Control - non-diabetic rats; Diabetic; Diabetic + insulin; Diabetic + melatonin. All treatments lasted 30 days. Diabetes was induced by streptozotocin (60mg/kg ip) and melatonin (10mg/kg, ip). Insulin was administered at a dose of 5 IU/day. In the histopathological analysis, the animals in groups II and III presented significant disorganization and vacuolization of cardiomyocytes with histopathological scores above 2 (moderate to extensive degeneration of cardiomyocytes with diffuse infiltration of inflammatory cells) and score 1 (mild; degeneration of cardiomyocytes with discrete infiltration of inflammatory cells), respectively. Morphometric analysis revealed a significant increase in cardiac wall thickness, reduction of the lumen and a higher lumen/wall thickness ratio in diabetic animals, in addition to presenting greater collagen staining and elevated levels of total creatine kinase, creatine kinase MB, lactate dehydrogenase, troponin, IL-6 and TNF-α, differing statistically from the other groups. These effects were prevented by melatonin. We conclude that melatonin has great potential as an adjuvant in preventing the development of diabetic cardiomyopathy in rats.